EFFECT OF EARLY VS. DELAYED CORD CLAMPING IN NEONATE'S HEART RATE AND OXYGEN SATURATION IN THE FIRST 10 MINUTES OF LIFE - ANWAR , A; NAQVI , Z (Biological and Clinical Sciences Research Journal, 2023)
The timing of umbilical cord clamping after birth can influence neonatal physiological parameters, which may affect immediate neonatal outcomes. This study sought to determine the effects of early cord clamping (ECC) and delayed cord clamping (DCC) on neonates' heart rate and oxygen saturation during the first ten minutes of life. The Obstetrics and Gynecology Department of Liaquat National Hospital, Karachi, carried out the randomized controlled trial with 200 participants. Two groups of newborns were assigned: ECC (cord clamped within 60 seconds of birth) and DCC (cord clamped after 60 seconds of birth). A pulse oximeter was used to monitor heart rate and oxygen saturation continuously from birth to 10 minutes of life. In most observed intervals, the heart rates of neonates in the DCC group fell within the range of 111 to 150 bpm. A significant proportion of ECC neonates had heart rates between 151 and 170 beats per minute at one minute. In addition, during the early postnatal period, DCC neonates consistently exhibited higher oxygen saturation levels, particularly within the 96-100% range, compared to ECC neonates. Delayed cord clamping appeared to promote stability in neonatal heart rate and enhance oxygen saturation in the immediate post-birth period. These findings highlighted the physiological advantages of DCC and its function in optimizing early neonatal outcomes.